Cleft Palate Associated with Hairy Polyp: A Case Report. (September 2013) - Desai, Anil; Kumar, Niranjan; Wajpayee, Madhukar; Jatania, Himanshu
Congenital tumors of the oral cavity are extremely uncommon, and hairy polyps are rare nonneoplastic growths. Most hairy polyps arise from the oronasopharynx and may cause impairment of the upper aerodigestive tract in newborns. Cleft palate is one of the most common congenital anomalies but its association with hairy polyp has been rarely reported. We report a case of hairy polyp with cleft palate and its management.